(untitled) (Mongolian Journal of Agricultural Sciences, 2025)
In recent decades, emerging and re-emerging diseases have been spreading worldwide. Lumpy skin disease is one of the most significant economic transboundary animal diseases. It has been reported in several areas of the world. The study supports the adoption of the portable Loop-Mediated Isothermal Amplification (vLAMP) assay as a primary diagnostic tool for lumpy skin disease virus. Main diagnostic methods such as Polymerase Chain Reactions (PCR) and Enzyme-Linked Immunosorbent Assay (ELISA) for detecting Lumpy Skin Disease (LSD) are sensitive and reliable but are often labor-intensive and time-consuming. In contrast, the portable vLAMP assay offers significant advantages for field application. It eliminates the need for specialized expertise or sophisticated laboratory equipment and can detect Lumpy Skin Disease Virus (LSDV) within 60 minutes under constant temperature conditions. This study aimed to develop and optimize a rapid, portable vLAMP assay for the on-site detection of LSDV. In addition, the sensitivity and specificity of this assay are comparable to conventional PCR and other tests. Thirty-two samples, including tissues, whole blood, serum, and swabs were analyzed using two DNA extraction kits and molecular methods: conventional PCR and vLAMP assay. The sensitivity and specificity of the vLAMP assay were estimated using a two-by-two contingency table and found to both be 100%. The vLAMP had a kappa value of 1.0 against the conventional PCR. Therefore, this vLAMP assay can be adopted as a timely and simple method for the early detection, monitoring, and control of LSDV outbreaks in field settings.